2017
DOI: 10.1007/s10973-017-6751-0
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy of formation of ye’elimite and ternesite

Abstract: Calcium sulfoaluminate clinkers containing ye'elimite (Ca 4 Al 6 O 12 (SO 4 )) and ternesite (Ca 5 (SiO 4 ) 2 SO 4 ) are being widely investigated as components of calcium sulfoaluminate cement clinkers. These may become low energy replacements for Portland cement. Conditional thermodynamic data for ye'elimite and ternesite (enthalpy of formation) have been determined experimentally using a combination of techniques: isothermal conduction calorimetry, X-ray powder diffraction and thermogravimetric analysis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Thermodynamic data for ye'elimite and ternesite are not included in the compilation of the title study as they are still being developed; however, current available data can be found in Refs. [8,67,[69][70][71].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Thermodynamic data for ye'elimite and ternesite are not included in the compilation of the title study as they are still being developed; however, current available data can be found in Refs. [8,67,[69][70][71].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Regarding thermodynamic modelling of CSA-based systems still some gaps are existing. There are several thermodynamic datasets for ye'elimite available in literature [32,[203][204][205], which need to be critically reviewed before including a consistent data set into thermodynamic databases. Such data would be needed e.g.…”
Section: Limitations Of Thermodynamicsmentioning
confidence: 99%
“…for calculating the hydration heat flow and the heat of hydration of ye'elimite-based systems, similar as previously done for Portland cement [206]. While thermodynamic data for ternesite was recently determined [41,205], such data seems to be missing for fluorellestadite.…”
Section: Limitations Of Thermodynamicsmentioning
confidence: 99%
“…The ternesite structure, as well as the formation and hydration characteristics of phases in the CaO-SiO 2 -CaSO 4 system, were subject to several studies [24][25][26][27]. Ternesite, a calcium-silicate-sulfate is isostructural with silicocarnotite [28,29] and is built up of isolated SiO 4 and SO 4 tetrahedra connected via calcium atoms that are 6-or 7-fold coordinated.…”
Section: Introductionmentioning
confidence: 99%